Soluble trace metals in aerosols over the tropical south-east Pacific offshore of Peru - Baker, A.R. (2016)
Meteor cruise M91 was supported by the BMBF projects SOPRAN II and III (FKZ 03F0611A and FKZ 03F662A). We thank the Peruvian authorities for authorising us to conduct the study in their territorial waters. We also would like to thank our Peruvian colleagues from IMARPE (M. Graco, A. Bernal, G. Flores, and V. León) for their logistical support to our work. Sample analysis was funded by the UK Natural Environment Research Council (NERC) through grant NE/H00548X/1 and by the School of Natural Sciences, University of East Anglia. We gratefully acknowledge the NOAA Air Resources Laboratory for the provision of the HYSPLIT transport and dispersion model and the READY website (http://www.arl.noaa.gov/HYSPLIT.php) and two anonymous reviewers for their comments on our manuscript.